High-entropy low-dielectric microwave ceramic

By using hexa-membered silicate and modified crystallized binder in silicate microwave ceramic materials, combined with the combination of modified boron glass powder and aminolated pearl powder, the problem of low mechanical strength of existing ceramic materials is solved, and the high mechanical properties and wide application of high entropy and low interstitial microwave ceramics are achieved.

CN119899026APending Publication Date: 2025-04-29KUNSHAN QINGYUAN ELECTRONIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510061717.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The binder of existing silicate microwave ceramic materials has poor deformation and diffusion capabilities under high temperature conditions, resulting in low mechanical strength of ceramic products and easy to break during operation, limiting its application range.

Method used

Hexa-membered silicate A2SiO4 and a modified crystallized binder, where A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and high entropy low interstitial microwave ceramics are prepared by wet grinding and sintering. The combination of modified boron glass powder and aminated pearl powder enhances the deformation ability and interface bonding strength of the binder.

Benefits of technology

It significantly improves the mechanical properties of ceramic materials, enhances its flexural strength and toughness, reduces the sintering temperature, improves the preparation efficiency, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899026A_ABST
    Figure CN119899026A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy low-dielectric microwave ceramic, and belongs to the technical field of electronic ceramic materials, and the high-entropy low-dielectric microwave ceramic is prepared by the following steps: step 1, mixing MgO, MnO, ZnO, CoO, CuO and NiO powder, taking deionized water as a grinding medium in a ball mill, and drying to obtain mixed powder 2; 2, citric acid and ethylene glycol are added into the mixed aqueous solution in parts by weight, heating and stirring are conducted, a mixed solution B is obtained, and solute in the mixed aqueous solution is MgCl2, ZnCl2, CuCl2 and NiCl2; and step 3, weighing silica powder in parts by weight, putting the silica powder into the mixed solution B obtained in the step 2, stirring, heating, filtering, then adding a crystallization binder and the mixed powder 2 obtained in the step 1, stirring, carrying out compression molding, and sintering to obtain the high-entropy low-dielectric microwave ceramic. The functions of the boron glass powder, the pyrophyllite and the aminated pearl powder in the prepared high-entropy low-dielectric microwave ceramic are mutually matched, so that the mechanical property of the prepared ceramic material can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic ceramic materials, and in particular to a high-entropy low-dielectric microwave ceramic. Background Art

[0002] Microwave dielectric ceramic material is a new type of multifunctional basic material, which is used as the basic element of functional components in communication system equipment. Among them, silicate microwave ceramic material has the advantages of low loss, adjustable resonant frequency temperature coefficient and low dielectric constant, which can meet the market demand for miniaturization, high frequency and low cost of communication equipment.

[0003] In the prior art, the binders used in silicate microwave ceramic materials have poor deformation and diffusion capabilities under high temperature conditions. They simply wrap the ceramic particles and it is difficult to form a strong connection system, resulting in low mechanical strength of the ceramic products and easy breakage during operation, which limits their application scope to a certain extent. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the deficiencies in the prior art, the present invention provides a high-entropy low-dielectric microwave ceramic, which solves the problems raised in the above-mentioned background technology.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A high-entropy low-dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of six elements of equimolar elements Mg, Co, Zn, Mn, Ni and Cu.

[0009] Furthermore, the molar amounts of the six elements Mg, Co, Zn, Mn, Ni and Cu in A are the same.

[0010] Furthermore, the method for preparing the high entropy low dielectric microwave ceramic comprises the following steps:

[0011] Step 1, mixing MgO, MnO, ZnO, CoO, CuO and NiO powders in an equal molar ratio, grinding them in a ball mill using deionized water as a grinding medium by wet grinding, and drying to obtain mixed powder 2;

[0012] Step 2, by weight, add 0.1 to 0.3 parts of citric acid and 1 to 2 parts of ethylene glycol to 50 to 100 parts of a mixed aqueous solution, heat to 60 to 80° C., and stir for 0.5 to 1 hour to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are equimolar MgCl2, ZnCl2, CoCl2, CuCl2, and NiCl2;

[0013] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 20 to 40 minutes, adjust the pH to 9 to 10 with sodium bicarbonate, continue stirring for 1 to 2 hours, heat to 60 to 80° C., filter, then add 1.2 to 1.3 parts of crystallization binder and 2 to 4 parts of mixed powder 2 obtained in step 1, stir for 10 to 20 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0014] The sintering process is to heat up to 1150-1350°C at a rate of 1-10°C / min, and the heat preservation time is 2-6 hours.

[0015] Furthermore, the preparation method of the crystallized adhesive comprises the following steps:

[0016] W1: Weigh modified borosilicate glass powder, amino pearl powder and pyrophyllite in a mass ratio of 10:0.3-0.5:1-2, mix them evenly to obtain a mixed powder 1, add a dextrin aqueous solution with a mass fraction of 1.0-1.2% to the mixed powder 1, stir for 10-20 minutes, and obtain a mixed slurry, wherein the mass of the dextrin aqueous solution is 2-2.4% of the mass of the mixed powder 1;

[0017] W2: The mixed slurry in W1 is pressed and calcined at a temperature of 400-500°C for 1.5-2.5 hours. The mixture is cooled, crushed, ball-milled, and sieved through a 200-mesh screen to obtain a crystallized binder.

[0018] Furthermore, the preparation process of the modified boron glass powder comprises the following steps:

[0019] S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a solution with a mass fraction of 0.3-0.5%, adding acetic acid, and adjusting the pH to 3-5 to obtain a modified solution;

[0020] S2: Mix borosilicate glass powder and nano-zirconia in a mass ratio of 50:2-3 to obtain mixed powder 3, then add the mixture to the modified solution prepared in S1, stir for 20-40 minutes, filter out the liquid, and dry it in an oven at 60-80°C for 2-10 hours to obtain modified borosilicate glass powder. The mass ratio of the modified solution to the mixed powder 3 is 5-10:1.

[0021] Furthermore, the treatment process of the amination pearl powder comprises the following steps:

[0022] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment in a nitrogen atmosphere at a treatment power of 165-175 W for a treatment time of 4-6 min to obtain pre-treated powder;

[0023] Q2: By weight, the pretreated powder in Q1 is placed in 80-120 parts of a 0.5-1% sodium dodecylbenzene sulfonate aqueous solution, stirred for 3-10 minutes, 0.6-1.0 parts of N-(2-hydroxyethyl)ethylenediamine and 0.5-0.7 parts of triethylamine are added, heated to 75-85°C, stirred for reaction for 1-2 hours, filtered, and dried to obtain amino pearl powder.

[0024] Furthermore, in the step W1, the mass ratio of the modified boron glass powder, the amino pearl powder and the pyrophyllite is 10:0.4:1.5.

[0025] Furthermore, in step S2, the mass ratio of boron glass powder to nano zirconium oxide is 50:2.5.

[0026] Furthermore, the molar concentrations of the solutes MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.2-0.3 mol / L.

[0027] Furthermore, the particle size of the mixed powder 2 is less than 10 microns.

[0028] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0029] 1. Borosilicate glass powder has a relatively low softening point, which can significantly reduce the sintering temperature of ceramic materials and has a good fluxing effect. It can form a liquid phase at a relatively low temperature and can be prepared for deformation in the early stage. The present invention is modified so that it can produce a bonding effect with the surface of pyrophyllite. At the same time, nano zirconium oxide can undergo a phase transition between a monoclinic phase and a tetragonal phase at different temperatures. This transition process will produce a volume change, which can cooperate with the volume change of the amino pearl powder to form compressive stress, reduce the generation of microcracks, and play a toughening effect.

[0030] 2. The present invention treats the surface of pearl powder with amino so that it can form a bond with the hydroxyl groups on the surface of pyrophyllite, making the bonding force between the powder particles stronger. The modified borosilicate glass powder, amino pearl powder and pyrophyllite cooperate with each other to diffuse the bonding phase from the high bonding phase area to the low bonding phase area, so that the hard particles can produce a pinning effect and particle reinforcement effect on the adhesive system with high viscosity, and can maintain a high interface bonding strength and density while adding the hard phase, so as to maintain a high toughness while achieving hardening, achieve high strength and toughness, and finally obtain a ceramic material with high mechanical properties.

[0031] 3. The binder system of the present invention has good deformation ability, high permeability and bonding ability, and can firmly pin the hard ceramic phase in the bonding system. The functions of borosilicate glass powder, pyrophyllite and amino pearl powder cooperate with each other, which can significantly improve the mechanical properties of the prepared ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Attached Figure 1 This is the XRD diagram of the high-entropy low-dielectric microwave ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0036] 1. Preparation of modified boron glass powder, including the following steps:

[0037] S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a solution with a mass fraction of 0.4%, adding acetic acid, and adjusting the pH to 4 to obtain a modified solution;

[0038] S2: Mix boron glass powder and nano zirconium oxide in a mass ratio of 50:2.5 to obtain mixed powder 3, then add it to the modified solution prepared in S1, stir for 30 minutes, filter out the liquid, and place it in an oven at 70°C for 6 hours to obtain modified boron glass powder. The mass ratio of the modified solution to the mixed powder 3 is 8:1.

[0039] 2. Performing amination treatment on the pearl powder to obtain amination pearl powder comprises the following steps:

[0040] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment under a nitrogen atmosphere at a treatment power of 170 W for a treatment time of 5 min to obtain pre-treated powder;

[0041] Q2: By weight, the pretreated powder in Q1 was placed in 100 parts of a 0.7% sodium dodecylbenzene sulfonate aqueous solution, stirred for 6 minutes, 0.8 parts of N-(2-hydroxyethyl)ethylenediamine and 0.6 parts of triethylamine were added, heated to 80°C, stirred for 1.5 hours, filtered, and dried to obtain amino pearl powder.

[0042] 3. Prepare a crystallized adhesive, comprising the following steps:

[0043] W1: Modified borosilicate glass powder, amino pearl powder and pyrophyllite were weighed in a mass ratio of 10:0.4:1.5, and mixed evenly to obtain a mixed powder 1. A dextrin aqueous solution with a mass fraction of 1.1% was added to the mixed powder 1, and stirred for 15 minutes to obtain a mixed slurry, wherein the mass of the dextrin aqueous solution was 2.2% of the mass of the mixed powder 1;

[0044] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 450°C for 2.0 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0045] 4. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0046] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0047] Step 2: In 75 parts of a mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added, by weight, and the mixture is heated to 70° C. and stirred for 0.7 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.25 mol / L;

[0048] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1.5 hours, heat to 70°C, filter, then add 1.25 parts of crystallized binder and 3 parts of mixed powder 2 obtained in step 1, stir for 15 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0049] The sintering process is to increase the temperature to 1250°C at a rate of 5°C / min and keep the temperature for 4 hours.

[0050] The XBD diagram of the high entropy low dielectric microwave ceramic prepared in Example 1 is as follows: Figure 1 shown.

[0051] Example 2

[0052] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0053] 1. Preparation of modified boron glass powder, including the following steps:

[0054] S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a solution with a mass fraction of 0.3%, adding acetic acid, and adjusting the pH to 3 to obtain a modified solution;

[0055] S2: Mix borosilicate glass powder and nano-zirconia in a mass ratio of 50:2 to obtain mixed powder 3, then add it to the modified solution prepared in S1, stir for 20 minutes, filter out the liquid, and dry it in an oven at 60°C for 2 hours to obtain modified borosilicate glass powder. The mass ratio of the modified solution to the mixed powder 3 is 5:1.

[0056] 2. Performing amination treatment on the pearl powder to obtain amination pearl powder comprises the following steps:

[0057] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment under a nitrogen atmosphere at a treatment power of 165 W for 4 min to obtain pretreated powder;

[0058] Q2: By weight, the pretreated powder in Q1 was placed in 80 parts of a 0.5% sodium dodecylbenzene sulfonate aqueous solution, stirred for 3 minutes, 0.6 parts of N-(2-hydroxyethyl)ethylenediamine and 0.5 parts of triethylamine were added, heated to 75°C, stirred for reaction for 1 hour, filtered, and dried to obtain amino pearl powder.

[0059] 3. Prepare a crystallized adhesive, comprising the following steps:

[0060] W1: Modified borosilicate glass powder, amino pearl powder and pyrophyllite were weighed in a mass ratio of 10:0.3:1, and mixed evenly to obtain a mixed powder 1. A dextrin aqueous solution with a mass fraction of 1.0% was added to the mixed powder 1, and stirred for 10 minutes to obtain a mixed slurry, wherein the mass of the dextrin aqueous solution was 2% of the mass of the mixed powder 1;

[0061] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 400°C for 1.5 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0062] 4. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0063] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0064] Step 2: In 50 parts of a mixed aqueous solution, 0.1 parts of citric acid and 1 part of ethylene glycol are added, by weight, and the mixture is heated to 60° C. and stirred for 0.5 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.2 mol / L;

[0065] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 20 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1, heat to 60°C, filter, then add 1.2 parts of crystallized binder and 2 parts of mixed powder 2 obtained in step 1, stir for 10 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0066] The sintering process is to heat up to 1150°C at a rate of 1°C / min and keep the temperature for 2 hours.

[0067] Example 3

[0068] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0069] 1. Preparation of modified boron glass powder, including the following steps:

[0070] S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a 0.5% solution by mass, adding acetic acid, adjusting the pH to 5, and obtaining a modified solution;

[0071] S2: Mix borosilicate glass powder and nano-zirconia in a mass ratio of 50:3 to obtain mixed powder 3, then add the modified solution prepared in S1, stir for 40 minutes, filter out the liquid, and dry in an oven at 80°C for 10 hours to obtain modified borosilicate glass powder. The mass ratio of the modified solution to the mixed powder 3 is 10:1.

[0072] 2. Performing amination treatment on the pearl powder to obtain amination pearl powder comprises the following steps:

[0073] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment under a nitrogen atmosphere at a treatment power of 175 W for 6 min to obtain pretreated powder;

[0074] Q2: By weight, the pretreated powder in Q1 was placed in 120 parts of a 1% sodium dodecylbenzene sulfonate aqueous solution, stirred for 10 minutes, 1.0 parts of N-(2-hydroxyethyl)ethylenediamine and 0.7 parts of triethylamine were added, heated to 85°C, stirred for 2 hours, filtered, and dried to obtain amino pearl powder.

[0075] 3. Prepare a crystallized adhesive, comprising the following steps:

[0076] W1: Modified borosilicate glass powder, amino pearl powder and pyrophyllite were weighed in a mass ratio of 10:0.5:2, and mixed evenly to obtain a mixed powder 1. A dextrin aqueous solution with a mass fraction of 1.2% was added to the mixed powder 1, and stirred for 20 minutes to obtain a mixed slurry, wherein the mass of the dextrin aqueous solution was 2.4% of the mass of the mixed powder 1;

[0077] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 500°C for 2.5 hours. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0078] 4. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0079] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0080] Step 2: Add 0.3 parts of citric acid and 2 parts of ethylene glycol to 100 parts of the mixed aqueous solution by weight, heat to 80°C, and stir for 1 hour to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CuCl2 and NiCl2 are all 0.3 mol / L;

[0081] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B in step 2, stir for 40 minutes, adjust the pH to 10 with sodium bicarbonate, continue stirring for 2 hours, heat to 80°C, filter, then add 1.3 parts of crystallization binder and 4 parts of mixed powder 2 obtained in step 1, stir for 20 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0082] The sintering process is to increase the temperature to 1350°C at a rate of 10°C / min and keep the temperature for 6 hours.

[0083] Example 4

[0084] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0085] 1. Preparation of modified boron glass powder, including the following steps:

[0086] S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a solution with a mass fraction of 0.35%, adding acetic acid, and adjusting the pH to 3.5 to obtain a modified solution;

[0087] S2: Mix boron glass powder and nano zirconium oxide in a mass ratio of 50:2.3 to obtain mixed powder 3, then add the modified solution prepared in S1, stir for 25 minutes, filter out the liquid, and place in an oven at 65°C for 4 hours to obtain modified boron glass powder. The mass ratio of the modified solution to the mixed powder 3 is 6:1.

[0088] 2. Performing amination treatment on the pearl powder to obtain amination pearl powder comprises the following steps:

[0089] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment under a nitrogen atmosphere at a treatment power of 168 W and a treatment time of 4.5 min to obtain a pre-treated powder;

[0090] Q2: By weight, the pretreated powder in Q1 was placed in 90 parts of a 0.6% sodium dodecylbenzene sulfonate aqueous solution, stirred for 4 minutes, 0.7 parts of N-(2-hydroxyethyl)ethylenediamine and 0.55 parts of triethylamine were added, heated to 78°C, stirred for 1.2 hours, filtered, and dried to obtain amino pearl powder.

[0091] 3. Prepare a crystallized adhesive, comprising the following steps:

[0092] W1: Modified borosilicate glass powder, amino pearl powder and pyrophyllite were weighed in a mass ratio of 10:0.35:1.2, and mixed evenly to obtain a mixed powder 1. A dextrin aqueous solution with a mass fraction of 1.08% was added to the mixed powder 1, and stirred for 13 minutes to obtain a mixed slurry, wherein the mass of the dextrin aqueous solution was 2.1% of the mass of the mixed powder 1;

[0093] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 420°C for 1.8 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0094] 4. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0095] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0096] Step 2, by weight, add 0.15 parts of citric acid and 1.2 parts of ethylene glycol to 60 parts of a mixed aqueous solution, heat to 66° C., and stir for 0.6 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CuCl2, and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CuCl2, and NiCl2 are all 0.22 mol / L;

[0097] Step 3. Weigh 5 parts of silicon powder by weight, place it in the mixed solution B of step 2, stir for 25 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1.2 hours, heat to 65°C, filter, then add 1.23 parts of crystallized binder and 2.5 parts of mixed powder 2 obtained in step 1, stir for 13 minutes, press into shape, and sinter to obtain high-entropy low-dielectric microwave ceramics, wherein the sintering process is to heat to 1160°C at a rate of 3°C / min, and the holding time is 3 hours.

[0098] Example 5

[0099] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0100] 1. Preparation of modified boron glass powder, including the following steps:

[0101] S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a solution with a mass fraction of 0.45%, adding acetic acid, and adjusting the pH to 5 to obtain a modified solution;

[0102] S2: Mix boron glass powder and nano zirconium oxide in a mass ratio of 50:2.8 to obtain mixed powder 3, then add it to the modified solution prepared in S1, stir for 35 minutes, filter out the liquid, and place it in an oven at 78°C for 9 hours to obtain modified boron glass powder. The mass ratio of the modified solution to the mixed powder 3 is 8:1.

[0103] 2. Performing amination treatment on the pearl powder to obtain amination pearl powder comprises the following steps:

[0104] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment under a nitrogen atmosphere at a treatment power of 173 W and a treatment time of 5.6 min to obtain pre-treated powder;

[0105] Q2: By weight, the pretreated powder in Q1 was placed in 110 parts of a 0.8% sodium dodecylbenzene sulfonate aqueous solution, stirred for 9 minutes, 0.9 parts of N-(2-hydroxyethyl)ethylenediamine and 0.65 parts of triethylamine were added, heated to 82°C, stirred for 1.8 hours, filtered, and dried to obtain amino pearl powder.

[0106] 3. Prepare a crystallized adhesive, comprising the following steps:

[0107] W1: Modified borosilicate glass powder, amino pearl powder and pyrophyllite were weighed in a mass ratio of 10:0.45:1.8, and mixed evenly to obtain a mixed powder 1. A dextrin aqueous solution with a mass fraction of 1.18% was added to the mixed powder 1, and stirred for 19 minutes to obtain a mixed slurry, wherein the mass of the dextrin aqueous solution was 2.3% of the mass of the mixed powder 1;

[0108] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 480°C for 2.4 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0109] 4. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0110] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0111] Step 2: In 90 parts of a mixed aqueous solution, 0.25 parts of citric acid and 1.8 parts of ethylene glycol are added, by weight, and the mixture is heated to 76° C. and stirred for 0.9 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.28 mol / L;

[0112] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B in step 2, stir for 35 minutes, adjust the pH to 10 with sodium bicarbonate, continue stirring for 1.8 hours, heat to 75°C, filter, then add 1.28 parts of crystallized binder and 3.5 parts of mixed powder 2 obtained in step 1, stir for 19 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0113] The sintering process is to increase the temperature to 1340°C at a rate of 9°C / min and keep the temperature for 5 hours.

[0114] Comparative Example 1

[0115] Different from Example 1, pyrophyllite is not added in the preparation of the crystallized binder.

[0116] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0117] 1. Preparation of modified boron glass powder, including the following steps:

[0118] S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a solution with a mass fraction of 0.4%, adding acetic acid, and adjusting the pH to 4 to obtain a modified solution;

[0119] S2: Mix boron glass powder and nano zirconium oxide in a mass ratio of 50:2.5 to obtain mixed powder 3, then add it to the modified solution prepared in S1, stir for 30 minutes, filter out the liquid, and place it in an oven at 70°C for 6 hours to obtain modified boron glass powder. The mass ratio of the modified solution to the mixed powder 3 is 8:1.

[0120] 2. Performing amination treatment on the pearl powder to obtain amination pearl powder comprises the following steps:

[0121] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment under a nitrogen atmosphere at a treatment power of 170 W for a treatment time of 5 min to obtain pre-treated powder;

[0122] Q2: By weight, the pretreated powder in Q1 was placed in 100 parts of a 0.7% sodium dodecylbenzene sulfonate aqueous solution, stirred for 6 minutes, 0.8 parts of N-(2-hydroxyethyl)ethylenediamine and 0.6 parts of triethylamine were added, heated to 80°C, stirred for 1.5 hours, filtered, and dried to obtain amino pearl powder.

[0123] 3. Prepare a crystallized adhesive, comprising the following steps:

[0124] W1: Weigh modified borosilicate glass powder and amino pearl powder in a mass ratio of 10:0.4, mix them evenly to obtain mixed powder 1, add 1.1% dextrin aqueous solution to the mixed powder 1, stir for 15 minutes, and obtain a mixed slurry, wherein the mass of the dextrin aqueous solution is 2.2% of the mass of the mixed powder 1;

[0125] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 450°C for 2.0 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0126] 4. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0127] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0128] Step 2: In 75 parts of a mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added, by weight, and the mixture is heated to 70° C. and stirred for 0.7 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.25 mol / L;

[0129] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1.5 hours, heat to 70°C, filter, then add 1.25 parts of crystallized binder and 3 parts of mixed powder 2 obtained in step 1, stir for 15 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0130] The sintering process is to increase the temperature to 1250°C at a rate of 5°C / min and keep the temperature for 4 hours.

[0131] Comparative Example 2

[0132] Different from Example 1, no amino pearl powder is added in the preparation of the crystallized adhesive.

[0133] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0134] 1. Preparation of modified boron glass powder, including the following steps:

[0135] S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a solution with a mass fraction of 0.4%, adding acetic acid, and adjusting the pH to 4 to obtain a modified solution;

[0136] S2: Mix boron glass powder and nano zirconium oxide in a mass ratio of 50:2.5 to obtain mixed powder 3, then add it to the modified solution prepared in S1, stir for 30 minutes, filter out the liquid, and place it in an oven at 70°C for 6 hours to obtain modified boron glass powder. The mass ratio of the modified solution to the mixed powder 3 is 8:1.

[0137] 2. Prepare a crystallized adhesive, comprising the following steps:

[0138] W1: Weigh modified boron glass powder and pyrophyllite in a mass ratio of 10:1.5, mix well to obtain mixed powder 1, add 1.1% by mass fraction of dextrin aqueous solution to the mixed powder 1, stir for 15 minutes, and obtain a mixed slurry, wherein the mass of the dextrin aqueous solution is 2.2% by mass of the mixed powder 1;

[0139] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 450°C for 2.0 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0140] 3. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0141] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0142] Step 2: In 75 parts of a mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added, by weight, and the mixture is heated to 70° C. and stirred for 0.7 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.25 mol / L;

[0143] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1.5 hours, heat to 70°C, filter, then add 1.25 parts of crystallized binder and 3 parts of mixed powder 2 obtained in step 1, stir for 15 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0144] The sintering process is to increase the temperature to 1250°C at a rate of 5°C / min and keep the temperature for 4 hours.

[0145] Comparative Example 3

[0146] Different from Example 1, in the preparation of the crystallized binder, the modified boron glass powder is replaced by boron glass powder.

[0147] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0148] 1. Performing amination treatment on pearl powder to obtain amination pearl powder comprises the following steps:

[0149] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment under a nitrogen atmosphere at a treatment power of 170 W for a treatment time of 5 min to obtain pre-treated powder;

[0150] Q2: By weight, the pretreated powder in Q1 was placed in 100 parts of a 0.7% sodium dodecylbenzene sulfonate aqueous solution, stirred for 6 minutes, 0.8 parts of N-(2-hydroxyethyl)ethylenediamine and 0.6 parts of triethylamine were added, heated to 80°C, stirred for 1.5 hours, filtered, and dried to obtain amino pearl powder.

[0151] 2. Prepare a crystallized adhesive, comprising the following steps:

[0152] W1: Weigh borosilicate glass powder, amino pearl powder and pyrophyllite in a mass ratio of 10:0.4:1.5, mix well to obtain mixed powder 1, add 1.1% dextrin aqueous solution to the mixed powder 1, stir for 15 minutes to obtain a mixed slurry, wherein the mass of the dextrin aqueous solution is 2.2% of the mass of the mixed powder 1;

[0153] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 450°C for 2.0 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0154] 3. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0155] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0156] Step 2: In 75 parts of a mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added, by weight, and the mixture is heated to 70° C. and stirred for 0.7 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.25 mol / L;

[0157] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1.5 hours, heat to 70°C, filter, then add 1.25 parts of crystallized binder and 3 parts of mixed powder 2 obtained in step 1, stir for 15 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0158] The sintering process is to increase the temperature to 1250°C at a rate of 5°C / min and keep the temperature for 4 hours.

[0159] Comparative Example 4

[0160] Different from Example 1, in the preparation of the crystallized binder, the modified boron glass powder is replaced by boron glass powder, and pyrophyllite is not added.

[0161] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0162] 1. Performing amination treatment on pearl powder to obtain amination pearl powder comprises the following steps:

[0163] Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment under a nitrogen atmosphere at a treatment power of 170 W for a treatment time of 5 min to obtain pre-treated powder;

[0164] Q2: By weight, the pretreated powder in Q1 was placed in 100 parts of a 0.7% sodium dodecylbenzene sulfonate aqueous solution, stirred for 6 minutes, 0.8 parts of N-(2-hydroxyethyl)ethylenediamine and 0.6 parts of triethylamine were added, heated to 80°C, stirred for 1.5 hours, filtered, and dried to obtain amino pearl powder.

[0165] 2. Prepare a crystallized adhesive, comprising the following steps:

[0166] W1: Weigh borosilicate glass powder and amino pearl powder in a mass ratio of 10:0.4, mix them evenly to obtain mixed powder 1, add 1.1% dextrin aqueous solution to the mixed powder 1, stir for 15 minutes, and obtain a mixed slurry, wherein the mass of the dextrin aqueous solution is 2.2% of the mass of the mixed powder 1;

[0167] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 450°C for 2.0 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0168] 3. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0169] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0170] Step 2: In 75 parts of a mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added, by weight, and the mixture is heated to 70° C. and stirred for 0.7 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.25 mol / L;

[0171] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1.5 hours, heat to 70°C, filter, then add 1.25 parts of crystallized binder and 3 parts of mixed powder 2 obtained in step 1, stir for 15 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0172] The sintering process is to increase the temperature to 1250°C at a rate of 5°C / min and keep the temperature for 4 hours.

[0173] Comparative Example 5

[0174] Different from Example 1, in the preparation of the crystallized adhesive, the modified boron glass powder is replaced by boron glass powder, and no amino pearl powder is added.

[0175] A high entropy low dielectric microwave ceramic comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of equimolar elements Mg, Co, Zn, Mn, Ni and Cu, and is prepared as follows.

[0176] 1. Prepare a crystallized adhesive, comprising the following steps:

[0177] W1: Weigh boron glass powder and pyrophyllite in a mass ratio of 10:1.5, mix well to obtain mixed powder 1, add 1.1% by mass fraction of dextrin aqueous solution to the mixed powder 1, stir for 15 minutes, and obtain a mixed slurry, wherein the mass of the dextrin aqueous solution is 2.2% by mass of the mixed powder 1;

[0178] W2: The mixed slurry in W1 was pressed and calcined at a temperature of 450°C for 2.0 h. The mixture was cooled, crushed, ball-milled, and passed through a 200-mesh sieve to obtain a crystallized binder.

[0179] 2. Finally, high entropy low dielectric microwave ceramics are prepared, including the following steps:

[0180] Step 1, MgO, MnO, ZnO, CoO, CuO and NiO powders are mixed in equal molar ratios, and deionized water is used as a grinding medium in a ball mill, and wet-grinded to a particle size of less than 10 microns, and dried to obtain a mixed powder 2;

[0181] Step 2: In 75 parts of a mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added, by weight, and the mixture is heated to 70° C. and stirred for 0.7 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2, and the molar concentrations of MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.25 mol / L;

[0182] Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1.5 hours, heat to 70°C, filter, then add 1.25 parts of crystallized binder and 3 parts of mixed powder 2 obtained in step 1, stir for 15 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics;

[0183] The sintering process is to increase the temperature to 1250°C at a rate of 5°C / min and keep the temperature for 4 hours.

[0184] The high-entropy low-dielectric microwave ceramics prepared in the embodiments of the present invention and the comparative examples were used as samples. The Hakki-Collemon dielectric resonant cavity method was used to test the relative dielectric constant εr and the quality factor Q×f of the samples using an Agilent 8753ES 40 GHz vector network analyzer. The temperature coefficient of the samples was tested using a temperature box method. The flexural strength was measured using a ceramic pressing test method. The results are shown in Table 1.

[0185] Table 1

[0186]

[0187] As can be seen from the data in Table 1, the high-entropy low-dielectric microwave ceramics prepared in Examples 1 to 5 have dielectric constants between 7.10 and 7.30, all belonging to the low dielectric constant range, quality factors greater than 108600, and low energy loss. It can also be seen that they have good mechanical properties.

[0188] It can be seen from Table 1 that the flexural strength of the high-entropy low-dielectric microwave ceramic prepared in Comparative Example 1 is 141.2 MPa, which is significantly lower than the flexural strength of the high-entropy low-dielectric microwave ceramic prepared in Example 1 of 182.3 MPa, proving that the addition of talc in the preparation process of high-entropy low-dielectric microwave ceramics can improve the mechanical strength of the obtained ceramic material.

[0189] The reason why the mechanical properties of the high-entropy, low-dielectric microwave ceramics prepared in Comparative Example 1 decrease is that pyrophyllite itself is a hydroxyl-containing layered aluminum silicate with good pressure transmission ability, which can improve the force transmission and force-bearing properties of ceramic materials.

[0190] The flexural strength of the high entropy low dielectric microwave ceramics prepared in Example 1, Comparative Example 3 and Comparative Example 4 is reduced in turn. By analyzing the preparation method of the high entropy low dielectric microwave ceramics in Comparative Example 3, it can be seen that the modification of the boron glass powder can improve the mechanical strength of the prepared ceramic material. The boron glass powder added to Comparative Example 4 on the basis of Comparative Example 1 is unmodified boron glass powder. Combined with the analysis of Comparative Example 3, it can be seen that pyrophyllite can synergistically improve the mechanical properties of the prepared ceramic material with the modified boron glass powder.

[0191] It can be seen from Table 1 that the flexural strength of the high entropy low dielectric microwave ceramic prepared in Comparative Example 5 is less than that of the high entropy low dielectric microwave ceramic prepared in Comparative Example 2 and Comparative Example 1, and the flexural strength of the high entropy low dielectric microwave ceramic prepared in Comparative Example 2 is less than that of the high entropy low dielectric microwave ceramic prepared in Example 1. No amino pearl powder is added to Comparative Example 2, and Comparative Example 5 replaces the modified boron glass powder with an equal amount of boron glass powder on the basis of Comparative Example 2. The data in the table prove that there is a synergistic effect between the modified boron glass powder and the amino pearl powder, and the synergy between the two can improve the mechanical properties of the prepared ceramic material.

[0192] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high entropy low dielectric microwave ceramic, characterized in that: The invention comprises hexabasic silicate A2SiO4 and a crystallized binder, wherein A is composed of six elements: Mg, Co, Zn, Mn, Ni and Cu.

2. The high entropy low dielectric microwave ceramic according to claim 1, characterized in that: The molar amounts of the six elements Mg, Co, Zn, Mn, Ni and Cu in A are the same.

3. A high entropy low dielectric microwave ceramic according to claim 1 or 2, characterized in that: The method for preparing the high entropy low dielectric microwave ceramic comprises the following steps: Step 1, mixing MgO, MnO, ZnO, CoO, CuO and NiO powders in an equal molar ratio, grinding them in a ball mill using deionized water as a grinding medium by wet grinding, and drying to obtain mixed powder 2; Step 2, by weight, add 0.1-0.3 parts of citric acid and 1-2 parts of ethylene glycol to 50-100 parts of a mixed aqueous solution, heat to 60-80° C., and stir for 0.5-1 h to obtain a mixed solution B, wherein the solutes in the mixed aqueous solution are equimolar MgCl2, ZnCl2, CuCl2, and NiCl2; Step 3, weigh 5 parts of silicon powder by weight, put it into the mixed solution B of step 2, stir for 20 to 40 minutes, adjust the pH to 9 to 10 with sodium bicarbonate, continue stirring for 1 to 2 hours, heat to 60 to 80° C., filter, then add 1.2 to 1.3 parts of crystallization binder and 2 to 4 parts of mixed powder 2 obtained in step 1, stir for 10 to 20 minutes, press and mold, and sinter to obtain high entropy low dielectric microwave ceramics; The sintering process is to heat up to 1150-1350°C at a rate of 1-10°C / min, and the heat preservation time is 2-6 hours.

4. The high entropy low dielectric microwave ceramic according to claim 3, characterized in that: The preparation method of the crystallized adhesive comprises the following steps: W1: Weigh modified borosilicate glass powder, amino pearl powder and pyrophyllite in a mass ratio of 10:0.3-0.5:1-2, mix them evenly to obtain a mixed powder 1, add a dextrin aqueous solution with a mass fraction of 1.0-1.2% to the mixed powder 1, stir for 10-20 minutes, and obtain a mixed slurry, wherein the mass of the dextrin aqueous solution is 2-2.4% of the mass of the mixed powder 1; W2: The mixed slurry in W1 is pressed and calcined at a temperature of 400-500°C for 1.5-2.5 hours. The mixture is cooled, crushed, ball-milled, and sieved through a 200-mesh screen to obtain a crystallized binder.

5. The high entropy low dielectric microwave ceramic according to claim 4, characterized in that: The preparation process of the modified boron glass powder comprises the following steps: S1: adding γ-aminopropyltrimethoxysilane to anhydrous ethanol to prepare a solution with a mass fraction of 0.3-0.5%, adding acetic acid, and adjusting the pH to 3-5 to obtain a modified solution; S2: Mix borosilicate glass powder and nano-zirconia in a mass ratio of 50:2-3 to obtain mixed powder 3, then add the mixture to the modified solution prepared in S1, stir for 20-40 minutes, filter out the liquid, and dry it in an oven at 60-80°C for 2-10 hours to obtain modified borosilicate glass powder. The mass ratio of the modified solution to the mixed powder 3 is 5-10:

1.

6. The high entropy low dielectric microwave ceramic according to claim 4, characterized in that: The treatment process of the amination pearl powder, The following steps are involved: Q1: 10 parts by weight of pearl powder were placed in a plasma device and subjected to plasma treatment in a nitrogen atmosphere at a treatment power of 165-175 W for a treatment time of 4-6 min to obtain pre-treated powder; Q2: By weight, the pretreated powder in Q1 is placed in 80-120 parts of a 0.5-1% sodium dodecylbenzene sulfonate aqueous solution, stirred for 3-10 minutes, 0.6-1.0 parts of N-(2-hydroxyethyl)ethylenediamine and 0.5-0.7 parts of triethylamine are added, heated to 75-85°C, stirred for reaction for 1-2 hours, filtered, and dried to obtain amino pearl powder.

7. The high entropy low dielectric microwave ceramic according to claim 4, characterized in that: In the W1 step, the mass ratio of the modified boron glass powder, the amino pearl powder and the pyrophyllite is 10:0.4:1.

5.

8. The high entropy low dielectric microwave ceramic according to claim 5, characterized in that: In the step S2, the mass ratio of boron glass powder to nano zirconium oxide is 50:2.

5.

9. The high entropy low dielectric microwave ceramic according to claim 3, characterized in that: In step 2, the molar concentrations of the solutes MgCl2, ZnCl2, CoCl2, CuCl2 and NiCl2 are all 0.2-0.3 mol / L.

10. The high entropy low dielectric microwave ceramic according to claim 3, characterized in that: The particle size of the mixed powder 2 is less than 10 microns.